Removal Efficiency of Acid Red 18 Dye from Aqueous Solution Using Different Aluminium-Based Electrode Materials by Electrocoagulation Process - Nurulhuda Amri; Ahmad Zuhairi Abdullah; Suzylawati Ismail (Universitas Gadjah Mada, 2020)
This work compares commercial aluminium electrode for use in the treatment of wastewater by electrocoagulation process against waste aluminium cans electrode. The applicability of the waste aluminium cans electrode was tested for decolorization of Acid Red 18 dye as a model pollutant. The batch electrocoagulation process using both types of electrode was conducted at a current density of 25 mA/cm2, a pH of 3, an initial concentration of 100 mg/L and 25 min of reaction time. The elemental composition and surface morphology of both electrode materials and the sludge produced were analyzed using SEM-EDX to establish the correlation between the properties and characteristics of both electrode materials with their dye removal performance. The results demonstrated that waste aluminium cans performed better than commercial aluminium electrode with a removal efficiency of 100% in 25 min of reaction time. This was due to the higher Al dissolution of waste aluminium cans electrode that contributed to the larger amount of Al3+ released into the solution to consequently form more flocs to remove the dye molecules. In conclusion, the proposed waste aluminium electrode was considered as efficient and cost-effective and had the potential to replace the conventional ones in treating colored industrial wastewater using electrocoagulation process.